Physiological Performance, Antioxidant and Immune Status, Columnaris Resistance, and Growth of Nile Tilapia That Received Alchemilla vulgaris-Supplemented Diets - Abdallah Tageldein Mansour; Heba H. Mahboub; Gehad E. Elshopakey; Enas K. Aziz; Adnan H. M. Alhajji; Gamal Rayan; Hesham S. Ghazzawy; Walaa El-Houseiny (MDPI AG, 2022)
The current perspective is a pioneering trial to assess the efficacy of the dietary supplementation of Alchemilla vulgaris powder (AVP) in the diet of Nile tilapia (Oreochromis niloticus) on growth performance, blood picture, hepatic and renal biomarkers, immune status, and serum and tissue antioxidant capacity and to investigate the resistance against Flavobacterium columnare challenge. Fish (n = 360) were distributed into six groups (three replicates each) and received increasing AVP supplementation levels (0, 2, 4, 6, 8, and 10 g kg−1) for 60 days. Furthermore, fish were exposed to the bacterial challenge of a virulent F. columnare strain and maintained under observation for 12 days. During the observation period, clinical signs and the cumulative mortality percentage were recorded. The results demonstrated that the growth performance, feed conversion ratio, and hematological profile were noticeably enhanced in the AVP-supplemented groups compared to the control. The most promising results of weight gain and feed conversion ratio were recorded in the groups with 6, 8, and 10 g AVP kg−1 diets in a linear regression trend. The levels of hepatorenal function indicators were maintained in a healthy range in the different dietary AVP-supplemented groups. In a dose-dependent manner, fish fed AVP dietary supplements displayed significant augmented serum levels of innate immune indicators (lysozyme, nitric oxide, and complement 3) and antioxidant biomarkers (Catalase (CAT), superoxide dismutase (SOD), total antioxidant (TAC), and reduced glutathione (GSH) with a marked decrease in myeloperoxidase (MPO) and malondialdehyde (MDA) levels). Likewise, hepatic CAT and SOD activities were significantly improved, and the opposite trend was recorded with hepatic MDA. The highest AVP-supplemented dose (10 g/kg) recorded the highest immune-antioxidant status. Based on the study findings, we highlight the efficacy of AVP as a nutraceutical dietary supplementation for aquaculture to enhance growth, physiological performance, and immune-antioxidant status and as a natural economic antibacterial agent in O. niloticus for sustaining aquaculture. It could be concluded that the dietary supplementation of 10 g AVP/kg enhanced O. niloticus growth, physiological performance, immune-antioxidant status, and resistance against F. columnare.